PENGARUH PEMBERIAN MAKANAN PENDAMPING AIR SUSU IBU (MP-ASI) FORMULA TEMPE TERHADAP DIARE, AKTIVITAS FISIK, DAN PERTUMBUHAN, BAYI STATUS GIZI BAIK USIA 6 – 12 BULAN DI BOGOR JAWA BARAT - Atmawikarta, Arum (GIZI INDONESIA, 2007)
THE IMPACT OF TEMPE(FERMENTED SOYBEAN) BASEDCOMPLEMENTARY FOOD FORMULA ON DIARHEA,PHYSICAL ACTIVITY AND GROWTH AMONG 6-12YEARS OLD CHILDREN IN BOGOR, WEST JAVAMalnutrition is prevalent in developing countries including Indonesia. In more than 100 districts inIndonesia, children under five years old suffered from underweight (WAZ) at least 30 percent.Complementary food has beneficial for the children in preventing determinative condition.However, home made complementary food lack of micronutrients such as vitamin A, iron and zinc.Complementary food based on fermented soybean (tempe), coconut oil and skimmed milk socalled tempe formula, has distinctive effect in improving nutritional status and recovering diarheaeffectively among malnourished children. However, the effect of tempe formula on morbidity ofdiarhea, physical activity and growth of healthy children has not been recognized yet. This studyconsisted of 144 six-month old infants (SD±15 days) who was divided into two groups (72 infantseach) in a double blinded RCT. One group is allocated to receive tempe formula (FT) and theother group receive non-tempe complementary food (FBT). After five-month intervention, at theendline, there were 49 infants in FT group and 45 infants in non FT (FBT). During the study theenergy consumption of the infants increased according to age. The proportion of energyconsumption was about 27 to 46 percent of RDA and there was no significant difference betweentwo groups. The number of diarhea was fluctuative in the two groups, in cumulative number was 2or 3 episodes in both groups. There was no significant difference in number of diarhea episodebetween the two groups and so the length of the episode (between 8 and 10 days). There wasalso no difference in physical activity and motoric development and growth achievement betweentwo groups. The weight for height z-score of infants has decrease in both group. In conclusion, thestudy failed to show the benefical of tempe formula for healthy infants age 6-12 months in theepisode and length of diarhea growth and in physical activity but showed significant improvementof ferritin level.Keywords: complementary food, tempe, growth physical activity, children, fermented soybean